Peer-to-Peer Energy Trading Among Smart Homes Considering Demand Response - Gokcek, Tayfur; Erdinc, Ozan (IEEE, 2020)
In recent years, demand for energy and Distributed Generation (DG) resources has been increasing due to developing technology, increasing population density and environmental factors. Energy management, which is becoming more complex especially during the transformation process that renewable energy based DG units play an active role in, has revealed the smart grid concept. Thanks to this concept, consumers can both realize their consumption optimally with the smart home structure and actively participate in energy production with their own DG investments. In the last few years, one of the advantages offered by smart grid and smart home energy management to end consumers is the peer-to-peer (P2P) energy trading market, which means interpersonal. With this new energy market that has emerged, the participants who can make their own generation can sell their excess energy to other participants or to the power grid. In this paper, it is aimed to minimize the electricity bills of the end consumers by modeling the P2P energy trading structure in which the demand-side management is also taken into account. The proposed model was carried out in GAMS environment with CPLEX solver.
Keywords: OPERATION STRATEGY; MANAGEMENT; FRAMEWORK; SYSTEM; GENERATION; BUILDINGS; GRIDS; Engineering